Exílio, intelectuais, literatura e resistência política nas revistas Literatura Chilena en el Exilio/Literatura Chilena, Creación y Crítica e Araucaria de Chile (1977-1989) - Raphael Coelho Neto (2016)
In the context of the Chilean military dictatorship (1973-1990), Literatura Chilena en el Exilio/Literatura Chilena, Creación y Crítica has emerged as an exile magazine, whose first issue was published in Los Angeles, United States, by Ediciones de la Frontera publishing house in January 1977. It was founded and directed by Chilean writers and poets Fernando Alegría (1919-2005) and David Valjalo (1924-2005). The Araucaria de Chile magazine was founded in May 1977 on the initiative of exiled Chilean intellectuals, some of them with close ties to the Communist Party of Chile, as the politician, writer and essayist Volodia Teitelboim (1916-2008), who became its director, and also the editor and writer Carlos Orellana (1928-2013), who was appointed its editorial secretary. The existence of both magazines in exile for over 10 years, gathering in its pages an important of the Chilean and Latin America intelligentsia of that period, demonstrated the importance they had for the reception and dissemination of a cultural production politically marked by the resistance against Chile's Augusto Pinochet dictatorship. Thus, given the importance of Literatura Chilena and Araucaria de Chile magazines as instruments of cultural and political resistance policy in exile, we sought to develop a comparative study between them, aiming to explore how they debated and broadcasted ideas about the political exile, the role of the intellectuals and the political resistance literature from 1977 to 1989. The central purpose of this study is to understand the history and the collective project of these magazines through the proposed cut. Therefore, we aim to examine how their collaborators and their published texts dialogued with their programmatic editorials of the magazines, guided by the political resistance, and based on the values and ideals of the Chilean and Latin American Left.